Influence of carbon-based nanofillers on the melt flow singularity of linear polyethylene - Xu, Han; Lele, Ashish K.; Rastogi, Sanjay (Polymer, 2011)
A quantitative power law relationship between molecular weight and flow criticalities is uncovered that links stick-slip theory with the melt flow singularity observed during capillary flow. The singularity arises from decrease in pressure during melt flow of linear polyethylene through capillary die in a narrow temperature window. The molecular origin of the window effect is attributed to slip flow arising from disengagement of chains adsorbed to melt-wall interface from free chains in melt. Considering the similar molecular configuration of the linear polyethylene and carbon nanotubes (CNTs), the stretched chain conformation of the adsorbed chains in the presence of CNTs is influenced. The potential to broaden the window temperature interval in the presence of CNTs is explored. For the study, multi-walled carbon nanotubes (MWCNTs) are added in the linear polyethylene. The influence of the filler aspect ratio on the window effect is further investigated in the presence of carbon black (CBs). The presence of MWCNTs broadens the window temperature interval and increases the decrease in pressure. Contrary to MWCNTs in the presence of CBs the extrusion window narrows and reduction in the pressure-decrease occurs. It is also found that the two carbon nanofillers have a significant impact on flow-induced solidification. Both, the crystallisation rate and the onset temperature of crystallisation, increase with the loading of the two nanofillers. A closer comparison between the two carbon nanofillers at the same loading suggests that the crystallisation is more influenced in MWCNT-PE composites. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Capillary flow; Carbon fillers; Polyethylene

Ascertaining universal features of yielding of soft materials - Kamble, Samruddhi; Pandey, Anurag; Rastogi, Sanjay; Lele, Ashish K. (Rheologica Acta, 2013)
Many metastable complex fluids, when subjected to oscillatory shear flow of increasing strain amplitude at constant frequency, are known to show a characteristic nonlinear rheological response which consists of a monotonic decrease in the elastic modulus and a nonmonotonic change in the loss modulus. In particular, the loss modulus increases from its low strain value, crosses the elastic modulus, and then decreases with further increase in the strain amplitude. Miyazaki et al. (Europhys Lett 75:915-921, 2006) proposed a qualitative argument to explain the origin of the nonmonotonic nature of the loss modulus and suggested that in fact this response could be universal to all complex fluids if they are probed in a certain frequency window in which the fluid is dominantly elastic in the small strain limit. In this letter, we confirm their hypothesis by showing that a wide variety of complex fluids, irrespective of their thermodynamic state under quiescent conditions, indeed show the aforementioned characteristic nonlinear response. We also show that the maximum relative dissipation during yielding occurs when the imposed frequency resonates with the characteristic beta relaxation frequency of the fluid.
Keywords: Colloidal suspensions; Entangled melts; Gels; Glasses; Microgels; Rheology; Yielding

SANS and SAXS investigation of the melt state structure in disentangled ultrahigh molecular weight polyethylene - Sharma, Aakash; Kruteva, Margarita; Willner, Lutz; Romano, Dario; Porcar, Lionel; Dulle, Martin; Zhou, Fuhai; Rastogi, Sanjay; Richter, Dieter (ACS Macro Letters, 2025)
Disentangled ultrahigh molecular weight polyethylene exhibits a time-dependent increase in rheology modulus when molten. This originates from its kinetically evolving heterogeneous microstructure consisting of disentangled and entangled regions. We report a quantitative analysis of this microstructure using X-rays and neutrons that capture the signatures of these regions. We analyze the absolute intensities to obtain the volume fraction and size distribution of the disentangled domains in the melt. Employing neutrons, we follow the changes in these parameters with time. The trends are qualitatively similar to those of the previous rheological observations. Our methodology also provides an experimental verification of the theoretical report by McLeish, T. C. B. Soft Matter 2007, 3 (1), 83-87, which predicts the presence of high density disentangled domains in a low density entangled matrix. The analysis presented here is a useful instrument for unveiling the origin of differences in the properties of polymers obtained through different processing routes.